Effects of a plant-based fatty acid supplement and a powdered fruit, vegetable and berry juice concentrate on omega-3-indices and serum micronutrient concentrations in healthy subjects. (17th August 2020) - Dams, Sebastian; Holasek, Sandra; Tsiountsioura, Melina; Edelsbrunner, Martin; Dietz, Pavel; Koefeler, Harald; Malliga, Daniela-Eugenia; Gürbüz, Ayse; Meier-Allard, Nathalie; Poncza, Brigitte; Lackner, Sonja; Schwarzenberger, Elke; et al.
Abstract: The major aim of this controlled, randomised, open-labelled, parallel-grouped, clinical trial was to investigate whether supplementation with different dosages of omega-3 fatty acids (0.5 g/d and 1 g/d) from a plant-based fatty acid supplement affected omega-3-indices (O3I) in well-nourished, healthy people. In addition, the combined ingestion of the plant-based fatty acid supplement, together with an encapsulated fruit, vegetable and berry (FVB) juice powder concentrate, was applied in order to observe the absorption of certain micronutrients and to examine some aspects related to the safe consumption of the products. The data demonstrate that the intake of only 0.5 g/day of omega-3 fatty acids from of a vegan supplement was able to increase the O3I significantly after 8 and 16 weeks. The combined ingestion with the FVB supplement concurrently increased serum concentrations of specific vitamins and carotenoids without effects on hepatic, kidney and thyroid function or changes in blood lipids.